Responding to Human Rights Violations in Africa Assessing the Role of the African Commission and Court on Human and Peoples’ Rights - Ssenyonjo, Manisuli (International Human Rights Law Review, 2018)
This article examines the main achievements and challenges of Africa’s two regional bodies established to ensure the implementation of human rights in Africa. It makes an assessment of the role of Africa’s oldest regional human rights body, the African Commission on Human and Peoples’ Rights (African Commission) in the last 31 years of its operation (from 1987–March 2018). It also considers the judicial role of the African Court on Human and Peoples’ Rights (African Court) in the last 12 years of its operation (from 2006–March 2018). The increasing contribution of both the Commission and the Court to the protection of human rights under the African Charter on Human and Peoples’ Rights is rarely subjected to scrutiny in mainstream human rights literature. The article is limited to the consideration of the Commission’s contribution with respect to: (i) decisions on admissibility of communications concerning mainly exhaustion of domestic remedies; (ii) decisions on merits of communications; (iii) adoption of resolutions, principles/guidelines, general comments, model laws and advisory opinions; (iv) special rapporteurs and working groups to deal with thematic human rights issues; (v) consideration of State reports and conducting on-site visits; and (vi) referral of communications to the African Court involving unimplemented interim measures, serious or massive human rights violations, or the Commission’s findings on admissibility and merits.
Keywords: African Commission/Court on Human and Peoples’ Rights; exhaustion of domestic remedies; communications; resolutions; general comments; advisory opinions; special rapporteurs; State reports; access to African Court